A general strategy for controllable synthesis of Ba3(MO4)2:Mn5+ (M = V, P) nanoparticles. Issue 17 (8th February 2017) - Zhang, Xiaowen; Li, Yang; Hu, Zhongliang; Chen, Zhi; Qiu, Jianrong
Abstract : The second near-infrared window (NIR-II, 1000–1400 nm) is ideal for fluorescence imaging. We report a facile synthesis approach to prepare Mn 5+ doped Ba3 (MO4 )2 (M = V, P) nanoparticles with emission in the NIR-II region for the first time. Abstract : The second near-infrared window (NIR-II, 1000–1400 nm) is ideal for fluorescence imaging owing to negligible tissue scattering and minimal autofluorescence. NIR-II luminescence nanophosphors are promising materials for fluorescence imaging. Mn 5+ is emerging as a new luminescent indicator owing to its typical NIR-I (800 nm) to NIR-II (1190 nm) downconversion luminescence. Herein, we report a facile synthesis approach to prepare Mn 5+ doped Ba3 (MO4 )2 (M = V, P) nanoparticles with a remarkably sharp emission peak around 1190 nm in the NIR-II region for the first time to our knowledge. The developed two-step approach based on efficient anion exchange reaction is able to not only stabilize the valence but also keep the controlled morphology and uniform size. It is highly possible that the general approach will provide a new perspective on synthesizing special valence ion doped nanosized materials.